Human immunodeficiency virus‐1/simian immunodeficiency virus infection induces opening of pannexin‐1 channels resulting in neuronal synaptic compromise: A novel therapeutic opportunity to prevent NeuroHIV. Issue 2 (9th May 2021) - Gorska, Anna Maria; Donoso, Maribel; Valdebenito, Silvana; Prideaux, Brendan; Queen, Suzanne; Scemes, Eliana; Clements, Janice; Eugenin, Eliseo
Abstract: In healthy conditions, pannexin‐1 (Panx‐1) channels are in a close state, but in several pathological conditions, including human immunodeficiency virus‐1 (HIV) and NeuroHIV, the channel becomes open. However, the mechanism or contribution of Panx‐1 channels to the HIV pathogenesis and NeuroHIV is unknown. To determine the contribution of Panx‐1 channels to the pathogenesis of NeuroHIV, we used a well‐established model of simian immunodeficiency virus (SIV) infection in macaques ( Macaca mulatta ) in the presence of and absence of a Panx‐1 blocker to later examine the synaptic/axonal compromise induced for the virus. Using Golgi's staining, we demonstrated that SIV infection compromised synaptic and axonal structures, especially in the white matter. Blocking Panx‐1 channels after SIV infection prevented the synaptic and axonal compromise induced by the virus, especially by maintaining the more complex synapses. Our data demonstrated that targeting Panx‐1 channels can prevent and maybe revert brain synaptic compromise induced by SIV infection. Abstract : We Identified that Pannexin‐1 channels are a new player in the pathogenesis of HIV/SIV and NeuroHIV. We demonstrated that blocking the opening of Panx‐1 channels after infection prevented immune and brain compromise, especially the loss of complex synapses within the brain. We propose that blocking Pannexin‐1 channels in the HIV‐infected population can prevent or revert the devastating consequences of the virus in the brain.